Inequity in Maternal and Child Health Care Utilization in Nigeria. (27th December 2017) - Nghargbu, Rifkatu; Olaniyan, Olanrewaju
Abstract: The study assesses the degree and patterns of horizontal inequity in maternal and child health care utilization in Nigeria. Horizontal inequity was estimated using concentration curves and a standardized concentration index, which was decomposed into need and non‐need variables to capture the major drivers of inequity in utilization. Maternal and child health care utilization was measured by antenatal visits, skilled delivery and immunization utilization. Four rounds of Nigerian Demographic and Health Survey (DHS) data (1999, 2003, 2008, 2013) were used. The results show a positive horizontal inequity index from 1999 to 2013; which indicates that there is pro‐rich inequity in utilization of antenatal, skilled delivery and immunization, respectively. The study concludes that there is higher and increasing inequity in maternal health care while inequity in utilization of child health care decreased over time with wealth status and education as the major non‐need drivers of inequity in utilization. Interventions to enhance women's wealth status and education could significantly improve equity in skilled delivery and antenatal care utilization. Hence wealth creation, women empowerment and education should be given more attention to improve the deteriorating equity in maternal health care utilization.